Untangling Nickel Downstreaming: A Political Economy Analysis of Indonesia’s Morowali Industrial Park - Jordy, Jordy (Austronesia Akademika, 2025)
Indonesia's policy to downstream its nickel industry represents a significant strategic shift aimed at increasing domestic value addition and strengthening its position in the global market. This article analyzes the political economy dynamics of this policy, with a specific focus on the Indonesia Morowali Industrial Park (IMIP) as the central hub of its implementation. This study employs a qualitative case study method, utilizing stakeholder analysis, a Power-Interest Grid, and SWOT analysis to dissect the complex interactions among various actors. The analysis is based on a comprehensive review of academic literature, government regulations, and civil society reports. The findings reveal the formation of a powerful